(3eHGOF GdGbJUGO GdOhdj (B/s - (3OQGR MGeO YHO GdeLjOs; (3GdSjO MLGRj, GdeQSi s ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2003)
(3GdbQhV GdYGeI,JWhQ GdacQ GdeGdj HGdfSHI ddSjGSI GdGFJeGfjI GdYGeI,CfhGY GdbQhV GdYGeI hNUGFUgG,GdBKGQ GdGbJUGOjI ddbQhV GdYGeI(B-(3GdGfaGb GdYGe,CgejI GdGfaGb GdYGe hJWhQ GdacQ GdGbJUGOj,eaghe GdfabI GdYGeI,JbSje GdfabGJ GdYGeI,eYGjjQ JhRjY GdGfaGb GdYGe,GdBKGQ GdGbJUGOjI ddfabGJ GdeUQj,ejRGfjI GdOhdI,eaghe ejRGfjI GdOhdI,OhQI GdejRGfjI GdYGeI,JbSjeGJ GdejRGfjI hJHhjHGJgG,GdQbGHI GdeGdjIs
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdeGdjs; (3GdbQhVs